EFEKTIVITAS PEMBANGUNAN JALAN LAYANG DALAM MENINGKATKAN KINERJA RUAS JALAN PADA PERLINTASAN SEBIDANG DENGAN ANALISIS VISSIM (STUDI KASUS: JALAN RAYA SERPONG-CISAUK) - Sarifudin, Fuad; Putri, Mukhlisya Dewi Ratna (Pondasi, 2024)
The development of road and transportation infrastructure in Tangerang Regency is crucial for economic growth. The increasing number of vehicles on Jalan Raya Serpong-Cisauk, without adequate infrastructure development, has led to traffic volumes exceeding capacity. The solution implemented to reduce queue length and delays is the construction of a flyover. This study employs quantitative and qualitative methods, with primary data including traffic volume, free flow speed, and side friction, while secondary data is sourced from relevant agencies. The analysis is conducted using PKJI, VISSIM, and SWOT methods. The results show an increase in road capacity after the construction of the Cisauk flyover, with a decrease in the Dj ratio from 2.38 to below 1.00, and improved LOS from F to C/B during holidays and D/C on weekdays. However, surrounding businesses experienced negative impacts, including revenue decline and business relocations.